Optimization of the flight test organization structure of batch-producted aircraft based on entropy theory. Issue 3 (May 2021) - Jun, Deng
Abstract: According to the characteristics of batch-produced aircraft flight test, this paper optimizes the traditional project-based organization structure, and innovatively proposes an organizational structure suitable for batch-produced aircraft test flight. Using entropy theory, an entropy model of flight test organization structure is established, and the model is used for calculation and analysis to provide quantitative data reference for the optimization of flight test organization structure.